Effect of Potting Medium Ingredients and Sieve Size on the Growth of Seedlings of Sandalwood (Santalum album L.) in Root Trainers - Annapurna, D.; Rathore, T. S.; Joshi, G. (Indian Forester, 2007)
Eight combinations of potting medium ingredients and five sieve sizes of potting medium were used to find their effect on seedling growth of Santalum album L. in 270 cc block type root trainers using Cajanus cajan as a primary host. Analysis of potting medium ingredients was also carried out to find their mechanical, physical and chemical properties to understand its impact on seedling growth. The best seedling growth in terms of height, collar diameter, total dry weight, shoot dry weight, root dry weight and root shoot ratio was observed in potting medium consisting sand: soil: compost in the ratio of 40:10:50. High level of compost and low level of sand (75:25) favoured shoot growth and collar diameter, but further increase in organic matter (compost + cocopeat) inhibited overall growth of seedlings. Potting media consisting rice husk and charcoal (7.5% each) exhibited poor growth. Low level of soil (10%) in the potting medium favoured less compaction, better plug formation and seedling growth. Sieve size had significant effect on seedling growth. Potting medium sieved through 6 × 6 holes/sq inch proved the best for overall growth of seedlings, followed by 8 × 8 holes/sq inch. Increase (4 × 4 holes/sq inch) or decrease (12 × 12 and 10 × 10 holes/sq inch) in sieve size of the potting medium resulted in poor growth of the seedlings. By integrating the results of potting medium and sieve size, quality seedlings of sandalwood can be obtained within six months in 270 cc root trainers.